Tissue oxidative damage mediates impairment on phosphotransfer network during thymol intake: Effects on hepatic and renal bioenergetics - Baldissera M.D. (2018)
© 2018 Elsevier B.V.Recent evidences demonstrated that ingestion of several monoterpenes cause hepatic and renal damage due to impairment on mitochondrial energy production, eliciting a collapse on adenosine triphosphate (ATP) synthesis and consequently impairment on bioenergetic homeostasis. Thus, the aim of this study was to evaluate whether phosphotransfer network, catalyzed by creatine kinase (CK), adenylate kinase (AK), and pyruvate kinase (PK), can be a pathway to explain hepatic and renal bioenergetics homeostasis impairment due to thymol ingestion. Daily intake of thymol (40 mg/kg) significantly cause a decreased kidney weight and relative kidney weight compared to control group. The same dose of thymol inhibited renal cytosolic and mitochondrial CK activity as well as renal PK activity compared to control group. Finally, thymol (40 mg/kg) elicited a significant increase on renal reactive oxygen species and lipid damage levels, as well as an inhibition on antioxidant capacity against peroxyl radicals and non-protein thiol levels, which did not occur liver. Doses of 10 and 20 mg/kg of thymol administered orally for 30 consecutive days non-changed these variables. Based on these evidence, the data supported that intake of a high dose of thymol severely inhibits cytosolic and mitochondrial CK activity, a crucial enzyme to maintain cellular energy homeostasis. Moreover, high dietary thymol intake impaired communication between CK isoenzymes, which inhibits the attempts to regenerate ATP or to facilitate the CK/PCr shuttle to improve the intracellular ATP utilization and consumption. Moreover, the inhibition of renal CK and PK activities appears to be mediated by the renal oxidation of lipids and thiol groups, as well as by the reduction of the renal antioxidant capacity.